2019
DOI: 10.1088/1748-9326/ab1c31
|View full text |Cite
|
Sign up to set email alerts
|

An update on the thermosteric sea level rise commitment to global warming

Abstract: The equilibrium thermosteric sea level rise caused by global warming is evaluated in several coupled climate models. The thermosteric sea level rise is found to be well approximated as a linear function of the mean ocean temperature increase in the models. However, the mean ocean temperature increase as a function of the mean surface temperature increase differs between the models. Our models can be divided into two branches; models with an Atlantic meridional overturning circulation that increases with warmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…At the end of the 21st century, the global glacier volume is projected to decrease by between 21 % (MMCP2.6) and 24 % (MMCP8.5) of its current value. The contribution to GMSL from glaciers and ice caps melting generally corroborates the findings by Hock et al (2019), who found that by the end of the 21st century mountain glaciers and ice caps lose between 11 %-25 % (RCP2.6) and 25 %-47 % (RCP8.5) of their volume. For scenario MMCP8.5, our results are below the average estimates at the end of the 21st century because of the rather low climate sensitivity in LOVECLIM.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At the end of the 21st century, the global glacier volume is projected to decrease by between 21 % (MMCP2.6) and 24 % (MMCP8.5) of its current value. The contribution to GMSL from glaciers and ice caps melting generally corroborates the findings by Hock et al (2019), who found that by the end of the 21st century mountain glaciers and ice caps lose between 11 %-25 % (RCP2.6) and 25 %-47 % (RCP8.5) of their volume. For scenario MMCP8.5, our results are below the average estimates at the end of the 21st century because of the rather low climate sensitivity in LOVECLIM.…”
Section: Discussionsupporting
confidence: 88%
“…Glaciers and ice caps are the second-largest contributor to present-day GMSL rise (after the thermosteric component) and will continue to be a major source of sea-level rise during the next century (Huss and Hock, 2015;Hock et al, 2019;Marzeion et al, 2020). At the end of the 21st century, the global glacier volume is projected to decrease by between 21 % (MMCP2.6) and 24 % (MMCP8.5) of its current value.…”
Section: Discussionmentioning
confidence: 99%
“…Levermann et al (2013) identified a similar linear relation between thermal expansion and global mean temperatures of 0.2 to 0.63 m per °C. Hieronymus (2019) assessed several coupled climate models and found an updated sensitivity of 0.51 to 0.83 m per ˚C of surface warming. The higher sensitivity is present in climate models that show an increase in AMOC strength.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the higher sensitivity reported by Hieronymus (2019) might be an overestimation in future scenarios where the ice sheets will melt strongly, due to the neglect of ice sheet-ocean interactions.…”
mentioning
confidence: 94%
“…To link the CDF for GMST increase by CP16 to global mean sea level (GMSL) rise, one needs a functional relationship between the two parameters. A linear relationship between GMST and GMSL has been found to hold on time scales of millennia [22,23]; however, for end of the current century projections, it is not evident what to use. Figure 9 (top) shows the GMSL projections (median and likely range) for RCPs 2.6, 4.5 and 8.5 relative to 1986-2005 from [1] plotted against the corresponding projected GMST increase relative to preindustrial from [24].…”
Section: Probabilities For a Baseline Scenariomentioning
confidence: 99%